Zmiany prawnopodatkowe w branży e-commerce – cele i perspektywy rozwoju regulacji - Bajdiuk, Klaudia (Wydawnictwo C.H. Beck, 2023)
The paper discusses the issues of cybernetic legal and tax changes in the e-commerce industry, including the objectives and further prospects for the development of regulations. The author brings up the subject of dynamic evolution of the trade industry and its consequences. She discusses in detail the four groundbreaking regulations that are the foundation for legal changes in regard to the sealing of the tax system in the current digital era, also considering the effects of implementing these legal acts into national legislation.
Keywords: e-commerce; era cyfrowa; prawo podatkowe; dyrektywa; platforma cyfrowa; podatek VAT; elektronizacja; ustawodawstwo; uszczelnienie systemu podatkowego